CHANGES IN THE MORBIDITY AND PREVALENCE OF MENTAL AND BEHAVIORAL DISORDERS OF CHILDREN LIVING IN THE WARZONE IN EASTERN UKRAINE - Volosovets, O.P.; Кryuchko, T.O.; Chernyshova, O.E.; Volosovets, A.O.; Trachuk, L.E.; Guryev, S.O.; Ostropolets, M.S.; Grischenko, N.V. (World of Medicine and Biology, 2021)
The article is devoted to the dynamics of morbidity and prevalence of mental morbidity and behavioral disorders of children in Donetsk and Luhansk regions, where war conflict is taking place. Also we wanted to compare this indicator to national ones and to determine the possible impact of the ongoing war on their development. Children from warzone have an increased morbidity and prevalence of mental morbidity and behavioral disorders in comparison with national levels. It has become possible due to chronic stress and other adverse factors. This situation requires creation and implementation of state and regional programs for medical, psychological and social support to children from these regions with mental morbidity and behavioral disorders, in order to improve their quality of life and social adaptation.
Keywords: children; mental and behavior disorders; warzone